SOSIALISASI POLITIK OLEH KOMISI PEMILIHAN UMUM PROVINSI DKI JAKARTA DALAM MEMBENTUK PEMILIH CERDAS PADA PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR DKI JAKARTA TAHUN 2017 - Herdian, Dindin; Redjo, Samugyo Ibnu; Djuyandi, Yusa (Al-Ijtima`i: International Journal of Government and Social Science, 2018)
This study analyzes political socialization by KPU Provinsi DKI Jakarta informing smart voters in the DKI Jakarta governor election in 2017. This was motivated by the low level of voter participation in 2007 and 2012 and the existence of SARA issues which led to the actions of Muslims. The theory used in this study is the Theory of Rush and Althoff where there are 3 methods of political socialization, namely imitation, instruction, and motivation. The method in this study is a qualitative method. The results of this study are political socialization by the KPU Provinsi DKI Jakarta informing smart voters carried out by imitation method, instruction, and motivation. Imitation is done to the beginner voter by way of face-to-face socialization, election camp and choir competition. Instructions were made to the segment of people with disabilities by way of face-to-face and public debate socialization to the first 3 rounds. The motivation was carried out on segments of religious groups, women's groups, suburban groups and professional groups by way of face-to-face socialization, public debates to the first 3 rounds and second-round public debates.